De Gustibus Non Est Disputandum: An Experimental Investigation - Utteeyo Dasgupta; Lata Gangadharan; Pushkar Maitra; Subha Mani (Institute for the Study of Labor (IZA), 2014)
The goal of this paper is to examine stability in preferences using the Stigler-Becker state-dependent framework. Using a randomized intervention that changes the opportunity sets of individuals we construct a unique panel data from an artefactual field experiment and evaluate whether the change in the state space influences our selected indicators of preferences: risk, competitiveness, and confidence. We find that there is considerable heterogeneity of preferences across individuals at a point in time; risk and competitive preferences inter-temporally are consistent with state-dependent preferences, while measures of confidence seem to depend on past experiences.
Keywords: C9; D01; D03; 330; preference stability; state contingent preferences; artefactual field experiment